Adhesion-independent synergy of monocytes and endothelial cells in cytokine production: regulation of IL-6 and GM–CSF production by PAF - C. Lacasse; S. Turcotte; D. Gingras; M. Rola-Pleszczynski (Mediators of Inflammation)
Co-Cultures of monocytes (MO) and endothelial cells (EC) were studied for their capacity to synergize in the production of interleukin-6 (IL-6) and granulocyte-macrophage colony-stimulating factor (GM–CSF), two cytokines potentially important in vascular physiopathology. Resting monocytes produced detectable amounts of IL-6 but no GM–CSF, whereas confluent EC produced significant quantities of GM–CSF, but minimal IL-6. In co-cultures without stimuli, additive synthesis of both cytokines was observed. When EC were pretreated, however, with either PAF, TNF or both stimuli, before addition of MO, synergistic production of IL-6 was observed. In contrast, GM–CSF production was not enhanced by coculture of monocytes with activated EC. When either cell population was fixed with paraformaldehyde or killed by freeze-thawing before addition to the co-culture, cytokine levels reverted to those produced by the unaffected population alone. On the other hand, separating the two cell populations by a cell-impermeable membrane in transwell cultures did not affect the synergistic production of the cytokines. Taken together, our data suggest that EC and MO can synergize in response to stimuli by producing IL-6 and that this synergy is dependent on the integrity of both cell populations, but independent of cell-cell contact.